2019
DOI: 10.31489/2019ph2/29-34
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of electromagnetic waves in anisotropic magnetoelectric medium

Abstract: In the article we consider porpagation and interaction of electromagnetic waves of different polarization, in anisotropic medium that is inhomogeneous along the Z axis with magnetoelectric effect of tetragonal, trigonal, and hexagonal symmetries are described by the structure of the matrix coefficients. The matricant structure of the original system of equations follows from the structure of coefficient matrix. In unlimited periodic structures, dispersion relations of electromagnetic waves are determined from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Методом матрицанта [1] проводятся теоретические исследования упругих волн [2,3], электромагнитных волн в анизотропных средах [4,5,6], а также волновые процессы в пьезоэлектрических, пьезомагнитных [7], магнитоэлектрических [8,9] Уравнение (1) в матричном виде…”
Section: Introductionunclassified
“…Методом матрицанта [1] проводятся теоретические исследования упругих волн [2,3], электромагнитных волн в анизотропных средах [4,5,6], а также волновые процессы в пьезоэлектрических, пьезомагнитных [7], магнитоэлектрических [8,9] Уравнение (1) в матричном виде…”
Section: Introductionunclassified
“…In uniaxial materials with epsilon(1)=epsilon(2), mu(1)=mu(2), analytical expressions are obtained for the components of two harmonic plane waves propagating with different refractive indexes [11]. Based on the method matriciant [12] EM wave propagation in elastic, thermoelastic anisotropic, anisotropic dielectric media, in anisotropic plates, and with magnetoelectric effect have been investigated [13][14][15][16]. The matriciant method is also employed to investigate propagation of spin waves, the waves in liquid crystals and wave propagation in thermoelastic media [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that these SEV are effectively generated by the attenuated total reflection method. Processes in elastic anisotropic and anisotropic dielectric media and propagation of waves in anisotropic plates, electromagnetic waves in media with magnetoelectric effect [14][15][16][17], and waves in liquid crystals and thermoelastic media [18][19][20] were considered in [13] using the matricant method. Results of uniform description of wave processes in media with different physicomechanical properties were reported at the XVth All-Russian School-Seminar "Physics and Application of Microwaves" named after A. P. Sukhorukov (Waves-2016) [21].…”
Section: Introductionmentioning
confidence: 99%